Processing, microstructure and mechanical properties of Al-based metal matrix composites reinforced with mechanically alloyed particles - Chaubey A.K.; Scudino S.; Mukhopadhyay N.K.; Eckert J. (My University, 2025)
Al-based composites reinforced with Mg-7.4%Al mechanically alloyed particles have been synthesized by hot pressing followed by hot extrusion. Microstructural characterization of the bulk samples reveals the phase transformation of the reinforced particles (Mg(Al)ss + γ-Al12Mg17) to the stable intermetallic β-Al3Mg2 phase which occurs during consolidation. The phase transformation leads to the increase of effective volume faction of the reinforcement along with strong interfacial bonding, which causes a significant increase of the strength of the composites retaining appreciable plastic deformation. The strengthening can be attributed to the reduction of ligament size and to the interface strengthening due to better interface bonding (load-transfer) between the Al-matrix and the reinforcing particles. Copyright © Materials Research Society 2016.